Assessing tritium internalisation in zebrafish early life stages: Importance of rapid isotopic exchange. (February 2022) - Arcanjo, Caroline; Maro, Denis; Camilleri, Virginie; Cavalié, Isabelle; Simon, Olivier; Beaugelin-Seiller, Karine; Carasco, Loïc; Orjollet, Daniel; Adam-Guillermin, Christelle; Gagnaire, Béatrice
Abstract: "It appeared that OBT content in organisms was low with an OBT/TFWT ratio of about 8% for both stages (24 hpf and 96 hpf)." Should be read as "It appeared that OBT content in organisms was low with an OBT/TFWT ratio of about 8% and 14% at 24 hpf and 96 hphf respectively".